Answer: The required matrix is
![T=\left[\begin{array}{ccc}-1&3\\2&4\end{array}\right] .](https://tex.z-dn.net/?f=T%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D-1%263%5C%5C2%264%5Cend%7Barray%7D%5Cright%5D%20.)
Step-by-step explanation: We are given to find the transition matrix from the bases B to B' as given below :
B = {(-1,2), (3, 4)) and B' = {(1, 0), (0, 1)}.
Let us consider two real numbers a, b such that
![(-1,2)=a(1,0)+b(0,1)\\\\\Rightarrow (-1,2)=(a,b)\\\\\Rightarrow a=-1,b=2.](https://tex.z-dn.net/?f=%28-1%2C2%29%3Da%281%2C0%29%2Bb%280%2C1%29%5C%5C%5C%5C%5CRightarrow%20%28-1%2C2%29%3D%28a%2Cb%29%5C%5C%5C%5C%5CRightarrow%20a%3D-1%2Cb%3D2.)
Again, let us consider reals c and d such that
![(3,4)=c(1,0)+d(0,1)\\\\\Rightarrow (3,4)=(c,d)\\\\\Rightarrow c=3,d=4.](https://tex.z-dn.net/?f=%283%2C4%29%3Dc%281%2C0%29%2Bd%280%2C1%29%5C%5C%5C%5C%5CRightarrow%20%283%2C4%29%3D%28c%2Cd%29%5C%5C%5C%5C%5CRightarrow%20c%3D3%2Cd%3D4.)
Therefore, the transition matrix is given by
![T=\left[\begin{array}{ccc}-1&3\\2&4\end{array}\right] .](https://tex.z-dn.net/?f=T%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D-1%263%5C%5C2%264%5Cend%7Barray%7D%5Cright%5D%20.)
Thus, the required matrix is
![T=\left[\begin{array}{ccc}-1&3\\2&4\end{array}\right] .](https://tex.z-dn.net/?f=T%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D-1%263%5C%5C2%264%5Cend%7Barray%7D%5Cright%5D%20.)